The Effectiveness of PBL and TPS Models on Learning Outcomes and Confidence Attitudes (Universitas Negeri Semarang, 2019)
This study aims to determine and analyze the improvement of learning outcomes and students' self-confidence with PBL and TPS models. This study uses an experimental research design with two group pre-test - post-test designs. The study population was fourth-grade students at Elementary School in East Pekalongan sub-district. Samples were taken by random sampling technique obtained by 114 children from Public Elementary School Klego 01 as many as 61 students, and Public Elementary School Poncol 2 as many as 53 students. Research data were taken from tests and observations. The data were analysed using t-test analysis, with SPSS 23 software. The results showed PBL models are more effective than TPS models on learning theme VIII sub-theme 3 learning 3 with t-test sig values < 0.05. The research concludes that the PBL and TPS models are effective in improving learning outcomes and students' self-confidence. The PBL model is more effective than the TPS model in improving student learning outcomes and self-confidence.